AB1266 Autoimmune diseases induced by biological agents used in patients with advanced cancer: a nationwide multicenter registry of cases diagnosed in daily practice (CBIOGEAS-SEMI). (12th June 2018) - Retamozo, S.; Pérez-Álvarez, R.; Gutiérrez-Gosálvez, I.; Herranz, M.T.; Prieto-González, S.; Robles-Marhuenda, A.; Brito-Zerón, P.; Aguilar Romo, E.M.; Yllera Gutiérrez, C.; Antolí-Royo, A.C.; Flores-Chavez, A.; Morcillo, C.; et al.
Abstract : Objectives: To characterise the development of autoimmune diseases triggered by the new biological therapies used as immunotherapy in patients with advanced cancer in a real-life clinical setting. Methods: In 2006, the Study Group on Autoimmune Diseases (GEAS) of the Spanish Society of Internal Medicine created the BIOGEAS project, a multicenter study devoted to collecting data on the use and safety of biological agents in adult patients. In December 2016, the cBIOGEAS-SEMI multicenter registry was formed with the aim of collecting patients with cancer treated with biological immunotherapies who developed autoimmune diseases. Results: By January 2018, the cBIOGEAS-SEMI Registry includes 40 patients (26 men and 14 women, mean age of 59.7 years) who developed 54 triggered autoimmune diseases, including interstitial lung disease (n=11), enterocolitis (n=8), hypophysitis (n=6), polyarthritis (n=4), thyroiditis (n=3), vasculitis (n=3), severe cutaneous involvement (n=3), adrenalitis (n=2), Sjögren syndrome (n=2), cardiomyopathy (n=2), pancreatitis (n=2), Guillain-Barre syndrome (n=2), hepatitis (n=2) and CNS involvement, sclerosing cholangitis, glomerulonephritis and sarcoidosis (one case each). Underlying neoplasia consisted mainly in pulmonary neoplasia (n=16), melanoma (n=11) and breast cancer (n=3). The main pharmacological groups of cancer immunotherapies included PD1 inhibitors (n=26), CTL4 inhibitors (n=7), growth factor/adhesion molecules inhibitors (n=4), combined PD1/CTL4 blockade (n=2) and TK inhibitors (n=1); biologics included nivolumab (n=20), ipilimumab (n=9), pembrolizumab (n=8), trastuzumab (n=3), catumaxomab (n=1) and vemurafenib/combimetinib (n=1). Glucocorticoids were used in all cases but 4, and 9 patients required intravenous methylprednisolone pulses); 5 patients required additional immunosuppressive therapies (intravenous immunoglobulins in 4, methotrexate in one). All cases responded to treatment with glucocorticoids except 4 patients who died (3 due to ILD and one due to neurological disease). Conclusions: A wide variety of systemic and organ-specific autoimmune diseases triggered by the new cancer immunotherapies is emerging. In this nationwide real-life Registry, immune checkpoint inhibitors are the biologics involved in nearly 90% of cases. We found an excellent response to glucocorticoids, with a poor prognosis in those patients who developed pulmonary and neurological autoimmune diseases. Disclosure of Interest: None declared